PUBLIC HEALTH as a medical speciality in the European Union (Part 2) - Wdowiak, Leszek; Kapka, Lucyna (Polish Journal of Public Health, 2009)
In the first section of the article published in Polish Journal of Public Health, the issues concerning public health as a medical speciality in the European Union (EU) were discussed. The term ‘community medicine’ was subject to interpretation, which is predominant in the EU countries as an equivalent of the speciality specified in Poland as public health. It was emphasized that there is no consistency concerning the programmes of specialisation and terminology pertaining to public health, and also the lack of standardisation of terms in this field. The second part of this presentation aims to discuss what obstacles and differences can be encountered during public health doctors’ educational process in UE. The specificity of the problems and characteristics of tasks associated with the adaptation of this medical speciality on the European scale are discussed, as well as closely related with this process prospects for its development. It should be emphasized that it is most important for the development and standardisation of the speciality in public health to elaborate a common strategy for the European programme of training of physicians. In order to achieve this goal it is necessary to determine the essential contents of specialisation in public health, co-ordinate the scope of the essence and organization of specialist training, and organize the European co-operation in the field of education and training of medical specialists in public health. The considerations pertaining to the competences for public health with relation to the tasks of this speciality lead to the creation of the possibilities for public health development. Developing of the lists of competences has become a strong stimulus for the communication between public health professionals and those responsible for the adaptation of the specialisation on the European scale. One of the organizational tasks which the decidents will face within the several subsequent years, will be the efforts to expand the sphere of effect of public health on the local, national and European levels, as the tasks realized in this area are varied and mutually independent. Therefore, for this much needed integration process it is indispensable, during the creation of the European system of competences for public health, to engage both institutions and universities dealing with the scope of public health problems (especially the staff), as well as specialists professionally engaged in this field of medicine.